2010
DOI: 10.1519/jsc.0b013e3181ddb111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Resistance Training Intensity on Indices of Oxidative Stress

Abstract: The purposes of this study were (a) to determine whether acute resistance exercise training (RET) induces oxidative stress, (b) to determine whether chronic RET decreases oxidative stress level at rest condition in previously untrained men, and (c) also to investigate how the RET intensity influences the training-induced oxidative stress response. Sixteen young men who did not have RET experience in the past were randomly divided in 2 groups. Hypertrophy-intensity group (n = 9) performed 3 sets of 12 repetitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 22 publications
1
36
1
9
Order By: Relevance
“…In a recent study, after 6 weeks of resistance exercise training in young males, GSH levels increased when measured at rest, independent of the training intensity [15]. In light of the results obtained, we may suggest that after-school exercise programs have lower intensity and are healthier, as they limit the OS production.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In a recent study, after 6 weeks of resistance exercise training in young males, GSH levels increased when measured at rest, independent of the training intensity [15]. In light of the results obtained, we may suggest that after-school exercise programs have lower intensity and are healthier, as they limit the OS production.…”
Section: Discussionmentioning
confidence: 64%
“…Generally, at rest, the ADS is effective at controlling circulating free radicals, limiting cellular damage [14]. However, it has been reported that acute aerobic exercise induces OS, whereas regular aerobic exercise decreases oxidant markers and increases antioxidant enzyme activities [15]. Nonetheless, a substantial debate still exists on this matter, mainly because of controversial findings; in fact, most studies undertaken analyzed the OS profile in professional athletes or sports players habituated to high-intensity agonistic competitions [16][17][18][19], but not in regular practice of exercise or in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…41 Egzersiz sırasında SR üretimi egzersizin tü-rüne, şiddetine ve süresine bağlıdır. [44][45][46] Bunun en önemli sebebi, farklı egzersiz türlerinin farklı enerji gereksinimlerinin olması ve bundan dolayı farklı oksijen tüketim seviyelerine neden olmasıdır. Bunun sonucunda dokularda oluşturdukları farklı mekanik streslerin etkisi ile farklı kaynaklardan SR üretimini tetiklemesidir.…”
Section: Egzersi̇z Ve Oksi̇dati̇f Stresunclassified
“…Por fim, cabe ressaltar que o treinamento físico regular de intensidade moderada exerce ação antioxidante 57,58 . Embora os marcadores de estresse oxidativo normalmente avaliados sejam plasmáticos ou séricos, é possível especular que essa ação antioxidante do exercício seja sistêmica e, como tal, atinja também o sistema nervoso central.…”
Section: Roedoresunclassified